Dietary diversity is associated with nutritional status of Orang Asli children in Krau Wildlife Reserve, Pahang - Chuah, E. Y.; Mohad Sharif, Zalilah; Chin, Yit Siew; Sulaiman, Norhasmah (Nutrition Society of Malaysia, 2012)
Introduction: It is known that dietary diversity improves diet quality and nutritional status of young children. This study aimed to determine the relationship between dietary diversity and nutritional status of Orang Asli children in Krau Wildlife Reserve. Methods: A total of 216 children from three Orang Asli sub-tribes (Jah Hut, Temuan and Che Wong) aged 1 to 6 years from 162 households in 16 villages participated in this cross-sectional study. Children and mothers were measured for body weight and height. Mothers were interviewed for household socio-demographic information and diet diversity of children in the last 7 days. Diet diversity score (DDS) was calculated based on 15 food groups. Results: There was a high prevalence of underweight (50.9%) and stunting (61.6%) in Orang Asli children. For mothers, 11.1%, 27.8% and 7.4% were underweight, overweight and obese, respectively. Mean DDS of children was 6.38 [95% CI-6.10, 6.65] of the possible 15. Higher DDS of children was significantly related to older age (p<0.05), the non Jahut sub-tribe (p<0.01) and longer maternal years of schooling (p<0.05). DDS was also positively related to weight-for-age z-scores (p<0.001) and height-for-age z-scores (p<0.05). Conclusion: Undernutrition remains a major nutrition problem among Orang Asli children living within the forest reserve. Efforts to promote dietary diversity should emphasise traditional and nutritious foods that could improve health and nutritional status of the Orang Asli children.